How Do Acquirers Retain Successful Target CEOs? The Role of Governance - Wulf, Julie; Singh, Harbir (Management Science, 2011)
The resource-based view argues that acquisitions can build competitive advantage partially through retention of valuable human capital of the target firm. However, making commitments to retain and motivate successful top managers is a challenge when contracts are not enforceable. Investigating the conditions under which target chief executive officers (CEOs) are retained in a sample of mergers in the 1990s, we find greater retention of better-performing and higher-paid CEOs—both measures of valuable human capital. We also show that the performance-retention link is stronger when the acquirer's governance provisions support managers and when the acquirer's CEO owns more equity. Although it is not common for acquirers to retain target CEOs, we argue that they are more likely to do so when their governance environment maintains managerial discretion. Based on a joint analysis of retention and governance, our findings are largely consistent with a managerial human capital explanation of retention. This paper was accepted by Bruno Cassiman, business strategy.